2014
DOI: 10.1002/2014jd022423
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric distributions and interannual variability of NOy produced by energetic particle precipitation in 2002–2012

Abstract: We investigate the interannual variability and hemispheric differences of reactive odd nitrogen produced by energetic particle precipitation (EPP‐NOy) and transported into the stratosphere and lower mesosphere during polar winters in 2002–2012. For this purpose, EPP‐NOy amounts derived from observations of the Michelson Interferometer for Passive Atmospheric Sounding by means of a tracer correlation method have been used. Southern hemispheric (SH) seasonal maximum EPP‐NOy amounts transported below the 0.02 hPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
76
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 43 publications
11
76
4
Order By: Relevance
“…These values are higher than in previous studies summarized in , which provide a range of zero to 1.5 Gmol per winter based on HALOE (Siskind et al, 2000;Randall et al, 2007) observations, but are in good agreement with studies based on MIPAS data Reddmann et al, 2010;Funke et al, 2014b). In Funke et al (2014b), the wintertime increase in EPP NO y due to the indirect effect is derived from MIPAS observations for every Northern Hemisphere and Southern Hemisphere winter covered by MIPAS observations (mid-2002-early 2012). To make these observations directly comparable to our model results, the increase in every Northern Hemisphere and Southern Hemisphere winter is derived from the model results by subtracting the lowest value in the preceding summer.…”
Section: Total No Ycontrasting
confidence: 46%
See 2 more Smart Citations
“…These values are higher than in previous studies summarized in , which provide a range of zero to 1.5 Gmol per winter based on HALOE (Siskind et al, 2000;Randall et al, 2007) observations, but are in good agreement with studies based on MIPAS data Reddmann et al, 2010;Funke et al, 2014b). In Funke et al (2014b), the wintertime increase in EPP NO y due to the indirect effect is derived from MIPAS observations for every Northern Hemisphere and Southern Hemisphere winter covered by MIPAS observations (mid-2002-early 2012). To make these observations directly comparable to our model results, the increase in every Northern Hemisphere and Southern Hemisphere winter is derived from the model results by subtracting the lowest value in the preceding summer.…”
Section: Total No Ycontrasting
confidence: 46%
“…Additionally, there are sporadic increases of more than 1 Gmol per event Table 2. Comparison of modeled EPP NO y (Gmol) with data derived from MIPAS (Funke et al, 2014b). For the models, the difference between the highest value of this winter minus the lowest value of the preceding summer is given; in brackets, the maximal value of the winter is given.…”
Section: Total No Ymentioning
confidence: 99%
See 1 more Smart Citation
“…However, since below 50 km NO x is partly converted into its reservoirs (Stiller et al, 2005) In a recent paper, Funke et al (2014a) provide quantitative estimates of the total amount of EPP-NO y for the years 2002-2012, also inferred from MIPAS measurements. In a subsequent paper, Funke et al (2014b) showed that the EPP IE, i.e., the descended EPP-NO y , is highly correlated with geomagnetic activity, as indicated by the A p index, in Southern Hemisphere (SH) winters and dynamically unperturbed Northern Hemisphere (NH) winters. This suggests that the indirect effect during those winters is driven by the EPP source strength rather than by variations of subsidence.…”
mentioning
confidence: 99%
“…The IMK-IAA algorithm is described by von Clarmann et al (2009) and Funke et al (2014), and the most recent version of the level 2 data (used in this study) is version 5. The IMK-IAA algorithm uses an iterative variant of Tikhonov regularization (Tikhonov, 1963) on species-dependent sets of microwindows.…”
Section: Mipasmentioning
confidence: 99%